Recuperación y edición de archivos DGN (ING) - Ramírez, Manuel (2004)
MicroStation® is one of the most used software in geomatics for computer aid designing (generally y known as CAD’s). Large amounts of digital information used in cadastral and photogrammetric systems are manipulated by the use of this software. Because of failures in the hardware or logic errors in the programs, it is common that files containing valuable information be damaged, with the need of generation of the same information over again. These kinds of failures represent expenses to the companies manipulating these data. The authors based on their personal experience provide a series of useful commands that allow the recovering and manipulation of the files created by MicroStation®, avoiding, in this way, the waste of time and economic resources when generating twice the same digital information.